A cross-sectional study of biotechnology awareness and teaching in European high schools - ARĞA, KAZIM YALÇIN (My University, 2010)
Undoubtedly, biotechnology has a tremendous impact on our daily lives As a result of this and in parallel to the advancement of knowledge in this field of applied research, consumer awareness of the potential benefits and risks of this technology has steadily increased, leading to a thorough investigation of the public perception of biotechnology in the past years Indeed, it has become clear that it is in the general interest of science and especially of applied research to inform the public of its advances A promising next step is to strengthen biotechnology communication in scholastic institutions In this paper, we investigate the perception of biotechnology in a specific target group, namely high-school students in the 16-20-year-old age range We conducted a questionnaire-based survey on a total of 1410 students in six European countries to investigate students\" perception, concern, scientific knowledge, and awareness Our data revealed some unexpected patterns of acceptance and concern about biotechnology Knowledge analysis indicated that pupils lack specific knowledge about biotechnological applications and their interest in biotechnology appeared to be linked to knowledge Analysis of specific questions about teaching practices at schools suggests that a better targeted choice in media as vehicles for information together with selected speakers could be instrumental in increasing students\" interest in science and more specifically in biotechnology
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Medicine; Health Sciences; Fundamental Medical Sciences; Biochemistry; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYASAL ARAŞTIRMA YÖNTEMLERİ; Biyoloji ve Biyokimya; Yaşam Bilimleri (LIFE); BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Mikrobiyoloji; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; BIOCHEMICAL RESEARCH METHODS; BIOLOGY & BIOCHEMISTRY; Life Sciences (LIFE); BIOTECHNOLOGY & APPLIED MICROBIOLOGY; MICROBIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; İlaç Keşfi; Biyokimya (tıbbi); Uygulamalı Mikrobiyoloji ve Biyoteknoloji; Yapısal Biyoloji; Moleküler Tıp; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Drug Discovery; Biochemistry (medical); Applied Microbiology and Biotechnology; Structural Biology; Molecular Medicine; Molecular Biology; Clinical Biochemistry; Cancer Research; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology